2019
DOI: 10.1063/1.5065476
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interaction between asymmetric ligand-capped gold nanocrystals

Abstract: Atomistic molecular dynamics simulations are performed to study the potential of mean force (PMF) between two asymmetric gold nanocrystals (NCs) capped by alkylthiols in a vacuum. We systematically investigate the dependence of the PMF on the sizes and capping ligand lengths of two NCs. The results show that the potential well depth scales linearly with increasing total length of two capping ligands on asymmetric dimers, but it hardly depends on the NC size. The predicted equilibrium distance between two asymm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…For dodecanethiol ( n = 12) ligands this formula gives F min ≈ −194.4 k B T , which is definitely a very strong cohesive energy. Subsequently, other studies have reported consistent results. Extensions to other shapes, such as tetrahedra and cubes, and characterization of many-body effects , are also relevant, but extending the results in this study to these more general situations does not raise any new conceptual issues, so we will not discuss them any further.…”
Section: Introductionmentioning
confidence: 55%
“…For dodecanethiol ( n = 12) ligands this formula gives F min ≈ −194.4 k B T , which is definitely a very strong cohesive energy. Subsequently, other studies have reported consistent results. Extensions to other shapes, such as tetrahedra and cubes, and characterization of many-body effects , are also relevant, but extending the results in this study to these more general situations does not raise any new conceptual issues, so we will not discuss them any further.…”
Section: Introductionmentioning
confidence: 55%
“…42 With the OTM, systems of nanocrystals with a coordination number of 6 or greater could be described well 42 for systems with smaller coordination numbers, the overlap cone model (OCM) was developed. 41 Several theoretical studies applied these models in MD simulations with united-atom approaches, where SH, CH 2 , and CH 3 groups were treated as united atoms, 41,43−47 revealing either strong 48 or little interdigitation 43,44,47 of the ligands. Furthermore, both Liu et al 46 and Liepold et al 47 found a significant correlation between the ligand coverage and the interparticle spacing of two alkanethiol-capped nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…Several theoretical studies applied these models in MD simulations with united-atom approaches, where SH, CH 2 , and CH 3 groups were treated as united atoms, , revealing either strong or little interdigitation ,, of the ligands. Furthermore, both Liu et al and Liepold et al found a significant correlation between the ligand coverage and the interparticle spacing of two alkanethiol-capped nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…These effective interactions are computed from fully atomistic molecular simulations of nanoparticles. In this regard there have been a number of studies previously reported [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] that have computed effective inter-particle interactions. These studies looked at various aspects of interactions between nanoparticles including length of ligand chains, role of solvent, three-body interactions, etc.…”
Section: Introductionmentioning
confidence: 99%